2020
DOI: 10.1039/d0nr02908d
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum carbide and oxycarbide from carbon-supported MoO3 nanosheets: phase evolution and DRM catalytic activity assessed by TEM and in situ XANES/XRD methods

Abstract: Nanosheets of molybdenum(vi) oxide supported on carbon spheres were carburized and utilized for the dry reforming of methane (DRM). A molybdenum oxycarbide phase was identified as active for DRM and characterised by XANES and TEM methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 60 publications
4
41
1
Order By: Relevance
“…The dry reforming of methane, (DRM, CH 4 + CO 2 ↔ 2CO + 2H 2 ) is an example of a particularly challenging reaction for Mo 2 C-based catalysts because it combines a CO 2 -rich feed with high operating temperatures (typically, 800 °C and above) 11 , 14 21 . Deactivation of Mo 2 C in DRM conditions proceeds oxidatively according to Mo 2 C + 5 CO 2 → 2 MoO 2 + 6 CO 11 , 17 , 18 and in order to mitigate it, dry reforming of methane is often conducted at elevated pressures (2–10 bar) 11 , 14 , 16 , 18 , 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dry reforming of methane, (DRM, CH 4 + CO 2 ↔ 2CO + 2H 2 ) is an example of a particularly challenging reaction for Mo 2 C-based catalysts because it combines a CO 2 -rich feed with high operating temperatures (typically, 800 °C and above) 11 , 14 21 . Deactivation of Mo 2 C in DRM conditions proceeds oxidatively according to Mo 2 C + 5 CO 2 → 2 MoO 2 + 6 CO 11 , 17 , 18 and in order to mitigate it, dry reforming of methane is often conducted at elevated pressures (2–10 bar) 11 , 14 , 16 , 18 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The dry reforming of methane, (DRM, CH 4 + CO 2 ↔ 2CO + 2H 2 ) is an example of a particularly challenging reaction for Mo 2 C-based catalysts because it combines a CO 2 -rich feed with high operating temperatures (typically, 800 °C and above) 11 , 14 21 . Deactivation of Mo 2 C in DRM conditions proceeds oxidatively according to Mo 2 C + 5 CO 2 → 2 MoO 2 + 6 CO 11 , 17 , 18 and in order to mitigate it, dry reforming of methane is often conducted at elevated pressures (2–10 bar) 11 , 14 , 16 , 18 , 21 . From a mechanistic standpoint, an ill-defined molybdenum oxycarbide phase (MoO x C y ) has been reported to play a key role in DRM 22 , as well as in the water-gas shift 23 , deoxygenation 24 , 25 , and CO 2 -to-methanol 8 conversion processes, suggesting that the partial oxidation of Mo 2 C is favorable for those reactions.…”
Section: Introductionmentioning
confidence: 99%
“…During the DRM process, the molybdenum carbide may be partially oxidized to the form of an oxycarbide. Kurlov et al [218] reported that the oxycarbidic phase Mo 2 C x O y exhibits high stability toward further oxidation to MoO 2 , and the increase in β-Mo 2 C/ Mo 2 C x O y active sites correlates with higher efficiency in the DRM reaction.…”
Section: Molybdenum Carbidementioning
confidence: 99%
“…7 For instance, catalysts based on molybdenum carbide (Mo2C) are active in DRM. [7][8][9][10] Advantages of carbide-based catalysts include high resistance to coking or sulfur poisoning as well as sintering resistance, 11,12 however, the high oxophilicity of early TMCs is a limitation as it often results in the deactivation of TMCbased catalysts under oxidizing atmospheres (CO2) at high temperatures via the formation of oxide phases. More specifically, depending on the operating conditions, (the total pressure, the partial pressure of CO2, temperature and the space velocity) bulk β-Mo2C DRM catalysts can be oxidized to MoO2 which has been linked to their deactivation.…”
Section: Introductionmentioning
confidence: 99%
“…7,13 In addition, the partial oxidation of Mo2C to an oxycarbide phase MoCyOy can trigger the competing RWGS reaction. 10,14 Approaches to yield nanostructured Mo2C dispersed on a support can results in catalysts with an improved performance relative to the unsupported bulk carbides. [14][15][16] Mo2C-based catalysts are typically obtained by the carburization of a molybdenum oxide precursor such as MoO3 (supported or unsupported).…”
Section: Introductionmentioning
confidence: 99%